Unraveling refugee entrepreneurship and its role in integration: empirical evidence from the hospitality industry. Issue 9 (27th July 2019) - Shneikat, Belal; Alrawadieh, Zaid
ABSTRACT: Refugee entrepreneurship has emerged as an economic activity that can potentially help refugees during their settlement and integration processes in the host countries. Only recently have refugee entrepreneurs received some attention in the academic debates. However, despite valuable research endeavors, empirical inquiry addressing the refugee entrepreneurship process remains limited. Specifically, the role of entrepreneurship in facilitating the integration process of refugees is still understudied. The present study draws on qualitative data collected through 29 semi-structured interviews with Syrian refugees venturing in the hospitality industry in Turkey. Using the RQDA package for qualitative data analysis, the findings reveal that refugees' motivations to venture cover a wide range of push and pull factors including survivability, desire for independence, and availability of resources. The findings also confirm that entrepreneurial activities help refugees integrate with the socio-economic fabric of the host country. The study also identified several factors facilitating and derailing refugee entrepreneurs' integration process. Implications and directions for future research are discussed.